Taxonomic and morphological studies on the genus Chrotogonus Serville, 1838 (Pyrgomorphidae: Orthoptera) from Pakistan, with reference to their habitats (Baghdad Science Journal, 2023)
Species of genus Chrotogonus (surface grasshoppers) are phytophagous and damaging to various economical important plants in their seedling stages. In order to know the biodiversity of surface grasshoppers, the detailed study has been conducted from four provinces of Pakistan. During this study, biodiversity, taxonomy, diagnosis, morphometric analysis, habitat, global distribution, and remarks of each species have been described. Total of 826 specimens were collected and sorted out into three species and three subspecies: C. (Chrotogonus) homalodemus homalodemus (Blanchard, 1836), C. (Chrotogonus) homalodemus (Blanchard, 1836), C. (Chrotogonus) trachypterus trachypterus (Blanchard, 1836), C. (Chrotogonus) trachypterus robertsi Kirby, 1914, C. (Chrotogonus) trachypterus (Blanchard, 1836) and C. (Chrotogonus) turanicus Kuthy, 1905 based on newly constructed morphological keys and previous literature. The species C. (Chrotogonus) turanicus presented as a new record from Pakistan.